The Essence of Scientific Concepts and the Role of Students in the Process of Understanding Comprehension (Eurasian Scientific Herald, 2023)
In this article, the problem of understanding the concept of content in primary school students is interpreted in its own way. The essence of scientific concepts is also highlighted in this process. The process of understanding students of educational texts is cited.